WYBRANE ASPEKTY KSZTAŁCENIA KOMPETENCJI MIĘKKICH NA PRZYKŁADZIE ABSOLWENTÓW KIERUNKU KOSMETOLOGIA - Ewa Dziewońska (Jesuit University Ignatianum in Krakow, 2016)
RESEARCH OBJECTIVE: The contemporary labour market places high demands on graduates of higher education who are looking for employment. There is a significant increase in employers' requirements in the area of professional competence. This paper aims to present selected aspects of education and developing soft skills by students and  university graduates on the example of cosmetology subject.   THE RESEARCH PROBLEM AND METHODS: The expectations of the labour market to graduates of higher education require a new approach for the development strategies and skills training at universities. Job offers contain, in addition to the requirements of the knowledge, experience, cognitive and linguistic skills - a number of desirable personality traits and interpersonal skills of the applicant, called soft skills. Scientific studies indicate a dynamically growing importance of soft skills, both in the process of recruiting new employees, as well as major determinants of employment stability and continuity of careers. The article presents some aspects of soft skills training and coaching courses organized for students and graduates of higher education on the example of cosmetology subject. The article attempts to organize the terminology associated with this issue  and then, based on the specifics of teaching adults, presents own experiences in the area of planning coaching courses.   THE PROCESS OF ARGUMENTATION This paper attempts to draw attention to the growing significance of university graduates' background to proffesions requiring high degree of soft skills. Schoolings using activating teaching methoods foster building competences abilities that ensure professional flexibility and adaptability and help functioning in life.   RESEARCH RESULTS The article is the preliminary recognition of the analyzed problem. Author continued research in the area of impact of the activating methods on the development of the soft skills.       CONCLUSIONS, INNOVATIONS AND RECOMMENDATIONS: Schoolings described in this paper are planned as optional classes not included in curriculum. It is worth to consider including selected trainings as electives adapted to competence profiles of fields of study.